Persepsi Merek Dalam Pemilihan Air Minum Dalam Kemasan (Studi Pada Mahasiswa Universitas Islam Balitar Blitar) - Denok Wahyudi Setyo Rahayu (Universitas Islam Balitar, 2020)
The brand becomes important for consumers in choosing a product. The wide range of bottled drinking water brands can give consumers an alternative choice of which products to consume. The purpose of this study was to determine the brand's perception for consumers in choosing bottled water products. The research method uses direct observation and questionnaires to students as consumers of bottled water at Balitar Islamic University. The research population was Balitar Islamic University students. The sampling technique uses accidental sampling, namely students who accidentally meet with researchers. The variable used is brand perception. The results showed that brand perception can influence consumers in choosing bottled water products. Aqua product is a brand of bottled drinking water that is in high demand by consumers, while Le Minerals, Cleo, Ades, and Vit are interested after Aqua. Other respondents tend to consume the bottled drinking water brand in turn because they consider all brands the same.